2021
DOI: 10.3390/bios12010017
|View full text |Cite
|
Sign up to set email alerts
|

Novel SH-SAW Biosensors for Ultra-Fast Recognition of Growth Factors

Abstract: In this study, we investigated a label-free time efficient biosensor to recognize growth factors (GF) in real time, which are of gran interesting in the regulation of cell division and tissue proliferation. The sensor is based on a system of shear horizontal surface acoustic wave (SH-SAW) immunosensor combined with a microfluidic chip, which detects GF samples in a dynamic mode. In order to prove this method, to our knowledge not previously used for this type of compounds, two different GFs were tested by two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…NT3 consists of 119 amino acids and possesses an IEP of 9.5 [ 268 ]. The kinetics of adsorption of NT3, from low bulk concentration (50 mg/mL), was successfully determined on a modified silica biosensor by Matatagui et al [ 269 ]. NT4/5 molecules form non-covalent homodimers.…”
Section: Macroionsmentioning
confidence: 99%
“…NT3 consists of 119 amino acids and possesses an IEP of 9.5 [ 268 ]. The kinetics of adsorption of NT3, from low bulk concentration (50 mg/mL), was successfully determined on a modified silica biosensor by Matatagui et al [ 269 ]. NT4/5 molecules form non-covalent homodimers.…”
Section: Macroionsmentioning
confidence: 99%
“…This was due to an increase in mass due to antibody-antigen affinity, which produced a change in surface acoustic wave rate and therefore a change in resonant frequency (Figure. 8c) 93 . Since d-amino acid levels are often associated with different neurological disorders, it is important to develop rapid and specific biosensors for the determination of d-serine.…”
Section: Detection Of Biomoleculesmentioning
confidence: 99%
“…8c). 93 Since d -amino acid levels are often associated with different neurological disorders, it is important to develop rapid and specific biosensors for the determination of d -serine. Pietrantonio et al 94 fabricated a SAW biosensor with a PLP-reduced d -serine dehydratase for the detection of d -serine levels (Fig.…”
Section: Real-time Biosensors Based On Sh-sawmentioning
confidence: 99%
“…The acoustic wave parameters, typically amplitude and/or phase, shift because of specific biomolecules' presence on the acoustic wave-guide. Matatagui et al [ 50 ] demonstrated that SAW is a very fast, sensitive and label-free detection method for the grow factor detection.…”
Section: Biosensor Technologymentioning
confidence: 99%